1994
DOI: 10.1111/1467-9566.ep11347322
|View full text |Cite
|
Sign up to set email alerts
|

Women's socio‐economic status and self assessed health: identifying some disadvantaged groups

Abstract: This paper uses data from the British Health and LifestyleSurvey to explore the relationship between women's overall assessment of their health and their occupation, employment status, household composition and household income. Logistic regression was used to predict the odds of assessing health as either 'good' or 'less-than-good'. These findings suggest that after controlling for age and the presence of a long-standing illness or disability, women's occupational group has the strongest influence on self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…Gender often gets "buried" in multivariate analysis, due to multicollinearity issues among the variables that characterize women caregivers such as lower income, unemployment, coresidence, and persistent societal expectations that women provide personal care (Brewer, 2001;Lang, 1995). In this study, gender on its own is a significant predictor of SAHS, which validates the work of other researchers who found that gender alone is a predictor of lower self-assessed health status for women in general (Macran et al, 1994), and that women caregivers have worse indicators of health status than their noncaregiving counterparts (Zhang et al, 2006). Again, the differential effects of caregiving on women's SAHS are of particular concern as most caregiving tasks are accomplished by women.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Gender often gets "buried" in multivariate analysis, due to multicollinearity issues among the variables that characterize women caregivers such as lower income, unemployment, coresidence, and persistent societal expectations that women provide personal care (Brewer, 2001;Lang, 1995). In this study, gender on its own is a significant predictor of SAHS, which validates the work of other researchers who found that gender alone is a predictor of lower self-assessed health status for women in general (Macran et al, 1994), and that women caregivers have worse indicators of health status than their noncaregiving counterparts (Zhang et al, 2006). Again, the differential effects of caregiving on women's SAHS are of particular concern as most caregiving tasks are accomplished by women.…”
Section: Discussionsupporting
confidence: 88%
“…In all three countries, however, a moderate to high income was the next best predictor of better SAHS, an almost universal finding among health economics researchers (see Craig, 2005;Kipp et al, 2008;Macran et al, 1994;Sacker et al, 2005;Wilson, Jerret, & Eyles, 2001) where the link between income inequality and health outcomes is well established. It is only in very recent studies that the relationship between income level and caregivers' well-being is beginning to be established (Mitrani, Vaughan, McCabe, & Feaster, 2008;Papastavrou, Charalambous, & Tsangari, 2009;Siefert, Williams, Dowd, Chappel-Aiken, & McCorkle, 2008;Vellone, Piras, Talucci, & Cohen, 2008).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, role enhancement theorists (Marks, 1977;Sieber, 1974;Thoits 1986) proposed that health is enhanced by participation in all socially valued activities, such as marriage, parenthood and employment. Overall, empirical support for the role enhancement hypothesis has been fairly consistent in that women who have enacted more roles have generally been found to be mentally healthier than those who have enacted fewer roles (Barnett & Hyde, 2001;Feld, 1963;Hibbard & Pope, 1991;Macran, Clarke, Sloggett & Bethune, 1994;Repetti, 1998;Repetti, Matthews & Waldron, 1989;Verbrugge, 1983;Waldron, Weiss & Hughes, 1998).…”
Section: Social Roles and Health: A Brief Reviewmentioning
confidence: 97%
“…Die Arbeit von Hunt [ 12 ] deutet auf einen Zusammenhang zwischen bezahlter Arbeit und psychischen Indispositionen hin, wobei hier keine Geschlechtsabhängigkeit festgestellt wurde. Die Untersuchung von Macran [ 13 ] hatte den Einfl uss von Beschäfti-gungsstatus, Familienstatus und Einkommen auf das Gesundheitsbewusstsein zum Thema. Es wurde unter anderem durch die Analyse der Daten des "British Health and Lifestyle Survey's" gezeigt, dass Arbeit und ökonomische Selbstständigkeit mit hoher Gesundheitseinschätzung korrelieren.…”
unclassified